Optimizing Social Media Intelligence for Countering Radicalism by the Subdirectorate of Counter-Narrative, Densus 88 - Aliviqo Pandu Virgantara; Surya Nita; Didik Novi Rahmanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This research explores the critical role of Social Media Intelligence (SMI) within the operational framework of the Subdirectorate of Counter-Narrative, Densus 88 AT Polri, in countering radicalism and terrorism in Indonesia. Utilizing qualitative exploratory methods, including in-depth interviews and document analysis, the study investigates the effectiveness of SMI in identifying, analyzing, and disrupting radical narratives on social media. Drawing on frameworks such as Crime Prevention Theory, Surveillance Theory, and Counterintelligence Theory, the research highlights how SMI facilitates early threat detection, network analysis, and the identification of harmful content, contributing to national security. The findings underscore the adaptability of SMI amidst evolving digital challenges, such as algorithm changes and data privacy concerns, while emphasizing opportunities for integrating AI and machine learning to enhance analytical precision. This study not only provides actionable insights for law enforcement agencies but also advances the academic discourse on leveraging technology for counter-terrorism in the digital era.